PENAPISAN FITOKIMIA, PENETAPAN KADAR NAFTOKUINON TOTAL, DAN AKTIVITAS ANTIFUNGI FRAKSI TIDAK LARUT ETIL ASETAT EKSTRAK ETANOL DAUN PACAR KUKU (Lawsonia inermis L.) TERHADAP Candida albicans ATCC 10231 - zainab zainab; Ainun Muthoharoh (Pharmaciana, 2015)
Candidiasis is an infection caused by Candida albicans. Synthetic treatment against Candida albicans has been developed, but reports of resistance to antifungal agents that there continue to emerge, and cause a  lot of  side effects. Pacar kuku (Lawsonia inermis L.) is one of  the  plants  that has antifungal activity. Chemical content of polyphenols inhibit candidiasis is a form of naphthoquinone. This  study  aimed  to test the antifungal activity of ethanolic extract  of  insoluble ethyl acetate fraction of  pacar kuku leaves  against Candida albicans. The ethanol extract was obtained  from the ethyl acetate extraction of previously fractionated with ethyl acetate. Identification of chemical compounds made with phytochemical  screening. Test antifungal activity against Candida albicans using microdilution method. Amphoterisin B infusion in doses 250 µg/ml with the  concentration  of 1,50 µg/ml, 0,75 µg/ml, 0,38 µg/ml, 0,19 µg/ml, 0,09 µg/ml, dan 0,05 µg/ml were used as standard solution. The parameters in this study are the Minimum Inhibitory Concentration (MIC) and Minimum Fungicidal Concentration (MFC). The concentration of the extract used in the MIC and MFC determination  were 80%, 40%, 20%, 10%, 5%, 2,5% (w/v). Identification of chemical compounds was performed using test tubes and assay on anthraquinone compounds. The results showed that the MFC of the ethanol extract is 40% w/v. The MIC and MFC of amphoterisin B were 0,09 µg/ml and 0,19 µg/ml respectively. The test tubes showed that the ethanol extract contains  polyphenols, saponins, and quinone. The naphtoquinone total content in the ethanol extract consecutively 7,97±0,14%.